Smart things to know about knowledge management - Koulopoulos, Thomas M. (Capstone ConnecticutUS, 1999)
Presents knowledge management as a 21st century business imperative. Defines knowledge management and other related concepts e.g. knowledge, information management, learning organization. Looks at the role of technology in facilitating knowledge management; and advises on how to address issues such as the ownership of knowledge; and, building a knowledge-sharing culture. Discusses the role and leadership requirements for knowledge leaders; and makes projections about the future of knowledge-based organizations.